Ovarian cancer ascites induces skeletal muscle wasting in vitro and reflects sarcopenia in patients - Jorne Ubachs; Wouter R.P.H. van deWorp; Rianne D.W. Vaes; Kenneth Pasmans; Ramon C. Langen; Ruth C.R. Meex; Annemarie A.J.H.M. vanBijnen; Sandrina Lambrechts; Toon Van Gorp; Roy F.P.M. Kruitwagen; Steven W.M. Olde Damink; Sander S. Rensen (Journal of Cachexia, Sarcopenia and Muscle, 2022)
Abstract Background Cachexia‐associated skeletal muscle wasting or ‘sarcopenia’ is highly prevalent in ovarian cancer and contributes to poor outcome. Drivers of cachexia‐associated sarcopenia in ovarian cancer remain elusive, underscoring the need for novel and better models to identify tumour factors inducing sarcopenia. We aimed to assess whether factors present in ascites of sarcopenic vs. non‐sarcopenic ovarian cancer patients differentially affect protein metabolism in skeletal muscle cells and to determine if these effects are correlated to cachexia‐related patient characteristics. Methods Fifteen patients with an ovarian mass and ascites underwent extensive physical screening focusing on cachexia‐related parameters. Based on computed tomography‐based body composition imaging, six cancer patients were classified as sarcopenic and six were not; three patients with a benign condition served as an additional non‐sarcopenic control group. Ascites was collected, and concentrations of cachexia‐associated factors were assessed by enzyme‐linked immunosorbent assay. Subsequently, ascites was used for in vitro exposure of C2C12 myotubes followed by measurements of protein synthesis and breakdown by radioactive isotope tracing, qPCR‐based analysis of atrophy‐related gene expression, and NF‐κB activity reporter assays. Results C2C12 protein synthesis was lower after exposure to ascites from sarcopenic patients (sarcopenia 3.1 ± 0.1 nmol/h/mg protein vs. non‐sarcopenia 5.5 ± 0.2 nmol/h/mg protein, P < 0.01), and protein breakdown rates tended to be higher (sarcopenia 31.2 ± 5.2% vs. non‐sarcopenia 20.9 ± 1.9%, P = 0.08). Ascites did not affect MuRF1, Atrogin‐1, or REDD1 expression of C2C12 myotubes, but NF‐κB activity was specifically increased in cells exposed to ascites from sarcopenic patients (sarcopenia 2.2 ± 0.4‐fold compared with control vs. non‐sarcopenia 1.2 ± 0.2‐fold compared with control, P = 0.01). Protein synthesis and breakdown correlated with NF‐κB activity (rs = −0.60, P = 0.03 and rs = 0.67, P = 0.01, respectively). The skeletal muscle index of the ascites donors was also correlated to both in vitro protein synthesis (rs = 0.70, P = 0.005) and protein breakdown rates (rs = −0.57, P = 0.04). Conclusions Ascites of sarcopenic ovarian cancer patients induces pronounced skeletal muscle protein metabolism changes in C2C12 cells that correlate with clinical muscle measures of the patient and that are characteristic of cachexia. The use of ascites offers a new experimental tool to study the impact of both tumour‐derived and systemic factors in various cachexia model systems, enabling identification of novel drivers of tissue wasting in ovarian cancer.